Evaluation of wooden materials deteriorated by marine-wood boring organisms in the Black Sea - Sivrikaya, H.; Hafizoglu, H.; Cragg, S. M.; Carrillo, A.; Militz, H.; Mai, C.; Borges, L. M. S. (2012)
Marine borers can destroy wooden structures exposed to the marine environment and cause great monetary loss. In the region of Amasra of the Black Sea in Turkey, ships continue to be built from wood, mainly Castanea sativa (sweet chestnut) and Quercus petraea (sessile oak) and therefore are subject to destruction by marine borers. Copper-chromium-arsenic (CCA), used to be one of the most common wood preservatives used in Turkey. However, in this area its e cacy against marine borers is unknown. e resistance of untreated and CCA-treated samples of chestnut, oak and Scots pine (Pinus sylvestris) was examined and a er twelve months evaluated in two ways, EN 275, and a non-destructive measurement for dynamic modulus of elasticity (MOE). Untreated samples, particularly Scots pine were severely attacked by Teredo navalis. Treated samples of oak and chestnut were moderately attacked while treated samples of Scots pine sapwood and heartwood were sound. Severity of wood boring attack determined using MOE showed a very good correlation with that determined by visual assessment in untreated wood, and a good correlation for treated wood. Dynamic MOE allows rapid on-site evaluation rather than measurements within a laboratory and also without causing damage to the structures being evaluated.